Does an interaction exist between ketamine hydrochloride and Becton Dickinson syringes?. Issue 4 (12th October 2016) - Closset, M; Hecq, J D; Gonzalez, E; Bihin, B; Jamart, J; Galanti, L
Abstract : Introduction: An international alert from Becton Dickinson (BD) has noted the possibility of interaction between several molecules and some syringes. The Centralized IntraVenous Additives Service of the institution was using 3 mL BD syringes to store ketamine HCl. This study evaluated the interaction between ketamine and these syringes. Method: A batch of BD syringes produced in Europe and left in quarantine from the day of the international alert has been tested at 22, 29, 36, 43 and 50 days of storage at room temperature. At each time, the pH of the solutions was measured. The solutions were inspected visually and by microscope, and spectrophotometric measurements were performed. The concentrations were measured by a validated ultra-high-performance liquid chromatography-diode array detector. Results: Neither physical change nor pH modification was observed during the study. According to a lower limit of the 95% unilateral CI on the mean >90% of the theoretical concentration, the solutions remain stable for at least 50 days. Conclusion: In our study conditions, ketamine can be stored for at least 50 days without risk of sorption with syringes.